Lapatinib prevents and ameliorates dermal fibrosis in bleomycin induced experimental scleroderma model - Karatepe, Berçem Afşar; Yolbaş, Servet; Yıldırım, Ahmet; Hoşgün, Derya; Özercan, İbrahim Hanifi; Önalan, Ebru; Koca, Süleyman Serdar (Malatya Turgut Özal Üniversitesi, 2024)
Background: Scleroderma is a connective tissue disease characterized by endothelial damage and diffuse interstitial fibrosis. Lapatinib, a tyrosine kinase inhibitor, is a 4-anilinoquinol derivative. It inhibits many important signalling pathways including MAPK and PI3K. As a result, it affects cell cycle progression, apoptosis, angiogenesis and cell adhesion. Materials and Methods: Mice with an average age of 6 weeks and a weight of 20-25 g were divided into 6 equal groups (n=10 in each group). Mice in the control group (group A and group D), which were not treated with bleomycin (BLM), received sc phosphate buffered saline (PBS) daily. BLM was dissolved in FTS and administered to mice in groups B and C for 3 weeks, and to mice in groups E and F at a dose of sc 100 ?L (100 ?g) daily for 6 weeks. Mice in groups A, B and C were sacrificed at the end of week 3; mice in groups D, E and F were sacrificed at the end of week 6 and tissue samples were collected for further analysis. The mRNA expressions of TGF-?1 and fibronectin-1 were determined by RT-PCR. Results: Repeated subcutaneous administration of BLM caused dermal inflammatory cell infiltration, increased skin thickness and dermal fibrosis at early and late stages. TGF-?1 and fibronectin-1 mRNA expressions were also evidently increased. In both prophylactic and therapeutic applications of lapatinib, TGF-?1 and fibronectin-1mRNA expressions decreased markedly. In addition, histopathological dermal necro- inflammation and fibrosis were reduced. Conclusions: Lapatinib may exert anti-fibrotic effects in BLM-induced dermal fibrosis model. Studies show that lapatinib is a potential therapeutic agent, but it needs to be confirmed with in vivo studies.

Amaç: Skleroderma, endotelyal hasar ve diffüz interstisyel fibroz ile karakterize bir bağ dokusu hastalığıdır.Lapatinib, 4-anilinoquinoline türevi olan bir tirozin kinaz inhibitörüdür. Böylece, MAPK ve PI3K gibi önemli pek çok yolağın akışını durdurur. Sonuç olarak, hücre siklus ilerlemesi, apoptoz, anjiogenez ve hücre adhezyonunu etkilemektedir.Çalışmamızın amacı, bleomisin (BLM) ile oluşturulmuş deneysel skleroderma modelinde lapatinib uygulamalarının profilaktik ve teröpatik etkinliklerinin belirlenmesidir Materyal ve Metot: Çalışmaya ortalama 6 hafta yaşında ve 20-25 gram ağırlıklarında, 6 eşit gruba ayrıldı (her grupta n=10).Bleomisin uygulanmayacak olan kontrol grubu farelere (grup A ve grup D), her gün sc fosfat ile tamponlanmış salin (FTS) uygulandı. BLM, FTS içerisinde çözündürülerek, B ve C grubundaki farelere 3 hafta boyunca, E ve F grubundaki farelere 6 hafta boyunca her gün sc 100 ?L (100 ?g) dozunda uygulandı. A, B ve C grup fareler 3. hafta; D, E ve F grubu fareler 6. hafta sonunda sakrifiye edildi ve yapılacak analizler için doku örnekleri alındı. Doku TGF-?1, ve fibronektin-1 mRNA ekspresyonları RT-PCR yöntemi ile belirlendi. Bulgular: Tekrarlanan subkutan BLM uygulamaları sonucunda; erken ve geç evrede, dermal inflamatuar hücre infiltrasyonu, dermal fibroz ve dermal kalınlıkta artış meydana geldi. Benzer şekilde TGF-?1 ve fibronektin-1 mRNA ekspresyonları belirgin artı. Lapatinibin hem profilaktik hem de teröpatik uygulamalarında TGF-?1, ve fibronektin-1 mRNA ekspresyonları belirgin azaldı. Ek olarak, histopatolojik olarak dermal nekro inflamasyon ve dermal fibrozda gerileme tespit edildi. Sonuç: Lapatinib BLM ile uyarılmış dermal fibroz modelinde anti-fibrotik etkiler sergileyebilmektedir.
Lapatinib bleomisin ile oluşturulmuş deneysel skleroderma modelinde dermal fibrozu önler ve iyileştirir
Keywords: Rheumatology and Arthritis; Romatoloji ve Artrit